Pengaruh Penggunaan Metode Qiroah Terhadap Prestasi Belajar Siswa Dalam Pelajaran Bahasa Arab di MDT Al-Qona’ah Kabupaten Bandung - Imam Asrofi; Acep Taryana (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2022)
Arabic is a very important language, without us knowing Arabic including the language used every day in worship practices like when praying. For Indonesian students have a background of the skills of reading Latin writing, the skills of reading Arabic writing are a problem, because Arabic alphabet is different from the Latin alphabet. The Qiroah method is a method carried out by presenting learning material by prioritizing reading, either by using voice or in the heart. With the Qiroah students, students are expected to be able to speak Arabic with fluent, right and smoothly according to the rules. The purpose of this study was to determine the application of the Qiroah method and the influence of the Qiroah method on student learning achievement in Arabic subjects. This study uses a quantitafif approach with the experimental method. Data collection techniques with observation, tests and documentation with samples taken are 36 students. The results of the study stated that there was an influence on the Qiroah method on student learning achievement indicated by an increase in the value of the pre-test and post-test. The difference in pre-test value with an average of 70.5 results increased to 78.5. The results of the hypothesis test that the researcher asked Ho rejected and Ha accepted was shown that t count = 17.33> T table = 1,687.